Ultrasonography and laparoscopy as a diagnostic tool for evaluation of genitalia in cows - SOFI, K A; SINGH, M M (The Indian Journal of Animal Sciences, 2018)
The present study was conducted for evaluating genitalia of cows (17) through transrectal ultrasonography (TRUS) and transabdominal laparoscopy (TAL) as a diagnostic tool. Genital tract of cows was initially examined by rectal palpation followed by TRUS and a day later TAL was conducted through flank approach.The study revealed: 35.3, 41.2 and 88.2% ovarian abnormalities; 5.8, 35.3 and 70.6% oviduct and adnexal abnormalities; and 23.6, 47.1 and 52.9% uterine abnormalities, by rectal palpation, TRUS and TAL, respectively. However, cervical abnormalities diagnosed were 35.3 and 52.9% by rectal palpation and TRUS respectively. TAL enabled to evaluate ovarian and oviduct and adnexal abnormalities accurately followed by TRUS than rectal palpation but ultrasound enabled to differentiate abnormalities like cystic ovaries, hydrosalpinx, pyosalpinx based on echogenicity compared to laparoscopy. However, TRUS proved to be very useful in diagnosing and differentiating uterine and cervical abnormalities compared to TAL and rectal palpation. It was concluded that both ultrasonography and laparoscopy are better diagnostic tools for evaluation of genitalia of bovines compared to rectal palpation and both these tools provided supplementary evidence in diagnosing and differentiating different genital abnormalities.